THE USE OF JIGSAW TYPE COOPERATIVE LEARNING MODEL TO IMPROVE CLASS IV PRIMARY SCHOOL COOPERATION SKILLS - Puspita, Anggun Trisna; Altaftazani, Deden Herdiana; Nurfurqon, Faridillah Fahmi (Journal Of Educational Experts (JEE), 2024)
The background of this research is to improve the collaboration skills of elementary school students, using the Jigsaw type cooperative model. This research used a mix method, with a sample of class IV students and a population of 30, consisting of 16 female students and 14 male students. The results of research data processing show that the average pretest score is 42.19, while the average posttest score is 86.28. Apart from that, the pretest normality test value is 0.066 while the posttest is 0.427, so significantly both values have met the normality test criteria, namely 0.05, meaning this research is acceptable. Furthermore, qualitatively, this research can be said to be successful, noting that there are difficulties or obstacles faced by teachers during learning, namely when conditioning students in conditions of moving from home groups and expert groups, because the atmosphere in the classroom is not conducive. So the conclusion of this research is that there has been an improvement with the implementation of the Jigsaw cooperative learning model for elementary school students.